From the past to the present: a view of teaching English as a Foreign Language (EFL) in Libya and the role of communicative language teaching (CLT) approach - Owen, Eman Abdussalam; Razali, Abu Bakar; Elhaj, Iman Abdussalam (Human Resource Management Academic Research Society, 2019)
In this this paper, the authors will highlight the history of the Libyan educational system in general and the English as a foreign language education in particular. The authors look into the role of the different policies and decisions from the Libyan Ministry of Education that shaped its education system, particularly on the teaching and learning of English as a foreign language, as it exists today. The authors give a review that explains the impact of Gaddaffi’s Regime on the Libyan education system and the problems, which arose at that time, and describe the history of the educational system since 1951 until the current education system used to date. Moreover, the authors discuss the history of English language teaching and the teaching methods used in the classroom with a background of how the communicative language teaching (CLT) approach was introduced in the Libyan classrooms. Finally, the authors will discuss the potentials and problems of CLT in the English language classroom.